2010
DOI: 10.1007/s11274-010-0444-1
|View full text |Cite
|
Sign up to set email alerts
|

Wheat (Triticum aestivum L.) growth enhancement by Azospirillum sp. under drought stress

Abstract: Plant growth promoting rhizobacteria (PGPR) can enhance plant growth by alleviating soil stresses. Although previously investigated, some new interesting details are presented regarding the alleviating affects of Azospirillum sp. on wheat growth under drought stress in this research work. We hypothesized that the isolated strains of Azospirillum sp. may alleviate the adverse effects of drought stress on wheat (Triticum aestivum L.) growth. Three different strains of Azospirillum lipoferum (B1, B2 and B3) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(120 citation statements)
references
References 44 publications
5
111
0
4
Order By: Relevance
“…In the other hand, the better development of plant root under drought stress after inoculation indicate the auxin production of bacteria should have increased but is still within the dose range beneficial for root development. We also investigated the production of both siderophore and acetoin which are also believed to be beneficial for drought resistance for host plants [25]. We observed that acetoin-producing bacteria also had beneficial effects on plant growth and drought resistance in wheat as strains 6-2, 6-7 and 6-12 did dramatically improve plant dry weight and root area.…”
Section: Discussionmentioning
confidence: 97%
“…In the other hand, the better development of plant root under drought stress after inoculation indicate the auxin production of bacteria should have increased but is still within the dose range beneficial for root development. We also investigated the production of both siderophore and acetoin which are also believed to be beneficial for drought resistance for host plants [25]. We observed that acetoin-producing bacteria also had beneficial effects on plant growth and drought resistance in wheat as strains 6-2, 6-7 and 6-12 did dramatically improve plant dry weight and root area.…”
Section: Discussionmentioning
confidence: 97%
“…Drought/water Azospirillum brasilense Sp245 Wheat, growth rate of coleoptiles [132] Drought Azospirillum brasilense INTA Az-39 wheat roots Wheat (T. aestivum) [133] Drought Azospirillum lipoferum Wheat (T. aestivum L.) [134] Drought Burkholderia phytofirmans Wheat (T. aestivum) Grain yield, photosynthetic rate, water use efficiency, chlorophyll content [135] Drought…”
Section: Bacterial Inoculate Properties Of the Crop Referencementioning
confidence: 99%
“…According to Arzanesh et al results, inoculation of wheat with Azospirillum spp. can alleviate drought stress on plant growth and yield through adjusting plant water characters [134].…”
Section: Droughtmentioning
confidence: 99%
“…As reported in Saxena and Tilak (1998), Yasari and Patwardhan (2007), Shaukat et al (2006) and Karthikeyan and Sakthivel (2011), bacteria of Azospirillum and Azotobacter could increase crop biomass, crop productivity, which contributed N nutrient through N 2 fixation at crop rhizosphere environment as well as phytohormone in direct manner. Moreover, studies from Yasari and Patwardhan (2007), Mehry et al (2008) and Arzanesh et al (2009) confirmed that application of Azospirillum was very effective in stimulating crop growth. Hindersah and Simarmata (2004) emphasize that Azotobacter bacteria have capability in producing phytohormone of auxin and cytochinine as well as supporting the soil function as growth media.…”
Section: Rice Crop Yieldmentioning
confidence: 88%